Development of a web mapping system for tourism attractive places in Bintulu, Sarawak / Sherrylyn Schinie Jilong ... [et al.] - Jilong, Sherrylyn Schinie; Abdul Rasam, Abdul Rauf; Ghazali, Rosmadi; Jaafar, Saiful Anuar; Saiful Bahry, Farrah Diana (Faculty of Information Management, 2023)
Tourism is one of the main sectors that has hugely contributed to Bintulu's economy by generating income from locals and foreign tourists that come to Bintulu for vacations. The rapid growth of digital technology has been affecting the tourism sector by making it easier for tourists to gain information about tourist attractions by computer or smartphone. This study was conducted to implement the knowledge and techniques from GIS and cartographic techniques to develop an electronic mapping system of tourism information in Bintulu. This proposed system was produced to support the usage of the Windows operating system for computers or laptops and the Android operating system that is compatible with the smartphone. This system maps system offered navigation functions in helping route users to locations or destinations. Developing a tourism information mapping system could help increase the integrity and accuracy of the data, especially the locations of the attraction places. Selected respondents have also satisfied with the functions proposed in the system.